Pengaruh Work From Anywhere Dan Mental Health Terhadap Kinerja Karyawan Pada Puskobankum BKN - Naufal, Ahmad (CV Warnak Johanna Nusantara, 2026)
This research aims to analyze the influence of Work From Anywhere (WFA) and Mental Health on employee performance at the Central Bureau of Personnel Legal Consultation and Assistance, National Civil Service Agency Headquarters. The research uses a quantitative approach with data collection through questionnaires distributed to the entire population of 40 employees, using a saturated sampling technique. The independent variables in this study are Work From Anywhere (WFA) and Mental Health, while the dependent variable is Employee Performance. The results of the t-test show that Work From Anywhere has a significant effect on employee performance, with a t-value of 6.471, greater than the t-table value of 2.02619, and a significance value of 0.000, which is less than 0.05. Thus, it can be concluded that Work From Anywhere significantly influences employee performance. Meanwhile, Mental Health does not have a significant effect, with a t-value of -1.389, less than the t-table value of 2.02619, and a significance value of 0.173, which is greater than 0.05. Therefore, it can be concluded that Mental Health does not significantly influence employee performance. The F-test results show that Work From Anywhere and Mental Health simultaneously have a significant effect on employee performance, with an F-value of 35.840, greater than the F-table value of 3.25. Based on the test criteria, with F-count > F-table at a significance level of 0.05, the null hypothesis (H03) is rejected, and the alternative hypothesis (Ha3) is accepted. Therefore, it can be concluded that Work From Anywhere (X1) and Mental Health (X2) simultaneously have a significant effect on employee performance (Y) at the National Civil Service Agency in Kramat Jati District, East Jakarta City. Keywords: Work From Anywhere (WFA), Mental Health, Employee Performance